Tracking the Identity of Moving Words: Stimulus Complexity and Familiarity Affects Tracking Accuracy - Jukka Hyönä; Lauri Oksama; Esa Rantanen (Wiley Online Library, 2025)
In two experiments, participants tracked the identity and location of moving words. The task bears resemblance to one performed by air traffic controllers who track multiple moving aircraft, where they are identified with relatively complex alphanumeric call signs. In Experiment 1, stimulus familiarity was manipulated by comparing the tracking of familiar words and pseudowords. In Experiment 2, also stimulus complexity was varied by having the participants track short and long words. Stimulus complexity affected tracking: short words were easier to track than long words. Moreover, familiarity of identity affected tracking of short words (short familiar words were easier to track than short pseudo‐words) but not of long words. The results are interpreted within the framework of the MOMIT model. Mathematical simulations suggest that observers may not have enough time for full identification of complex identities in a dynamic situation. Practical implications of the results for air traffic control are discussed.